Investigation of fractional-order pantograph delay differential equations using Sumudu decomposition method - Asrar Saleh Alsulami; Mariam Al-Mazmumy; Maryam Ahmed Alyami; Mona Alsulami (AIMS Mathematics)
This paper combines the Sumudu transform with the Adomian decomposition method to address Caputo-type fractional-order pantograph delay differential equations. It features numerical evaluations that confirm the effectiveness of the proposed methods. The study introduces a powerful computational technique for solving these equations, providing results that establish its efficiency and relevance through comparisons with existing methods. The findings underscore both the efficiency and accuracy of the proposed algorithm.